Ulna Fractures After Elbow Arthrodesis: A Report of 3 Cases. Issue 2 (April 2021) - Abdelaziz, Abed; Kanski, Gregory; Silver, Jacob; Ring, David; Mazzocca, Augustus D
Abstract : Elbow arthrodesis is an uncommon, typically last resort, salvage procedure to improve comfort and stability of the elbow. Case: Two surgeons performed 3 elbow arthrodesis at 90° elbow flexion secured with a plate and screws. All 3 patients experienced fracture at the most distal aspect of the posterior plate, consistent with a stress riser in this location. Conclusion: The risk of fracture is likely related to vulnerability of the arm with no elbow flexion and may not be ameliorated by changes in operative technique or bone quality. Ulna fracture can be anticipated after elbow arthrodesis and might further limit enthusiasm for elbow arthrodesis.